Career choices for obstetrics and gynaecology: recent updates from 40 years of national surveys of UK medical graduates. Issue 9 (September 2019) - Lambert, Trevor W; Smith, Fay; Goldacre, Michael J
Summary: Objective: To report doctors' early career choices for obstetrics and gynaecology, their eventual career destinations and factors influencing their career pathways. Design: Multi-cohort multi-purpose national questionnaire surveys of medical graduates in selected graduation years between 1974 and 2015. Setting: UK. Participants: UK-trained medical graduates. Main outcome measures: Career specialty choices; certainty about specialty choice; factors which influenced doctors' career choices; career specialty destinations 10 years after graduation. Results: Obstetrics and Gynaecology was the first choice of career for 5.7% of post-2002 graduates in year 1, 4.3% in year 3 and 3.8% in year 5. A much higher percentage of women than men specified Obstetrics and Gynaecology as their first choice: in year 1, 7.7% of women and 2.3% of men did so. The gender gap has widened since the 1970s and 1980s. In recent years, of those who specified Obstetrics and Gynaecology as their first choice in year 1 after graduation, 48% were working in Obstetrics and Gynaecology in year 10 (63% of men, 45% of women). Looking backwards from career destinations, 85% of doctors working in Obstetrics and Gynaecology in year 10 had specified Obstetrics and Gynaecology as a first, second or third choice of preferred career in year 1. Conclusions: Interest in Obstetrics and Gynaecology among UK graduates appears to be exceeding the demand for new specialists. Policy needs to address risks of over-production of trainees and ensure that some graduates interested in Obstetrics and Gynaecology consider alternative careers. The large gender imbalance should encourage consideration of the reasons for men choosing Obstetrics and Gynaecology in falling numbers.